Meningkatkan Hasil Belajar IPS Melalui Metode Card Sort Siswa Kelas V SD Negeri 2 Tongkuno Kabupaten Muna - Wa Ode Zalniyati; Muhammad Nawir; Rubianto Rubianto (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
Improving Social Studies Learning Outcomes Through the Card Sort Method for Class V Elementary School 2 Tongkuno, Muna Regency. Thesis. Elementary school teacher education major. Faculty of teacher training and education, University of Muhammadiyah Makassar. Supervisor I Muhammad Nawir and advisor II Rubianto.The main problem in this study is the low social studies learning outcomes of fifth grade students at SD Negeri 2 Tongkuno, Muna Regency. The purpose of this study was to improve social studies learning outcomes at Tongkuno 2 Public Elementary School, Muna Regency.This type of research is classroom action research (CAR), which consists of two cycles and each cycle is held in three meetings. Research procedures include planning, implementing actions, observation, and reflection. The subjects in this study were fifth grade students of SD Negeri 2 Tongkuno, Muna Regency, for the 2022/2023 academic year, with a total of 20 students. 9 men and 11 women. Data collection techniques through observation techniques, tests and documentation. Data analysis techniques were carried out through descriptive statistics.The results showed that there was an increase in social studies learning outcomes for fifth grade students at SD Negeri 2 Tongkuno, Muna Regency. Seen in the pre-cycle the average value obtained was 61 with a classical completeness percentage of 35% then in the first cycle the average value obtained was 64.75 with a classical completeness percentage of 35% and in the second cycle it increased with an average value 83.5 with a classical completeness percentage of 90%.From the results of this analysis it was concluded that using the Card Sort method could improve the learning outcomes of fifth grade students at SD Negeri 2 Tongkuno, Muna Regency.